2021
DOI: 10.3389/fped.2021.560720
|View full text |Cite
|
Sign up to set email alerts
|

Age and Gender-Specific Reference Intervals for Uric Acid Level in Children Aged 5–14 Years in Southeast Zhejiang Province of China: Hyperuricemia in Children May Need Redefinition

Abstract: Context: Hyperuricemia is defined when the plasma uric acid concentration is above 416 μmol/L (7 mg/dl) in male adults, or 357 μmol/L (6 mg/dl) in female adults. However, there are no explicit criteria yet for children.Objective: It is necessary to set up reference intervals for the uric acid level in different age groups among children.Materials and Methods: A total of 5,439 individuals (3,258 males, 2,181 females) were included in the final statistical analysis. Reference values of all age groups were determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 18 publications
2
14
0
1
Order By: Relevance
“…Females and children whose mothers had high education levels were less likely to have hyperuricemia. The level of uric acid increased with age in children aged 5-14 years in southeast China [47]. One study showed that boys had higher mean serum uric acid concentrations than girls [19], and this difference was consistent with our results.…”
Section: Discussionsupporting
confidence: 91%
“…Females and children whose mothers had high education levels were less likely to have hyperuricemia. The level of uric acid increased with age in children aged 5-14 years in southeast China [47]. One study showed that boys had higher mean serum uric acid concentrations than girls [19], and this difference was consistent with our results.…”
Section: Discussionsupporting
confidence: 91%
“…It has been reported that the levels of UA were similar between genders before puberty, but UA levels are higher in boys after puberty than in girls due to the action of sex hormones. It is generally believed that testosterone can inhibit the excretion of UA while estrogen can promote the excretion of UA ( 55 ). In our study, there was no statistical difference between genders.…”
Section: Discussionmentioning
confidence: 99%
“…In childhood, high values of UA are in uenced by ethnicity, age and sex, so a universal de nition of abnormal UA levels is lacking. In non-obese youths values above 6 or 7 mg/dL in boys and 5 or 6 mg/dL in girls were previously been considered "elevated" [18,19].…”
Section: Discussionmentioning
confidence: 99%